Deployment of A Data Consolidation System in an Aeronautical Administration: Application to the Rva/City of Kananga in the Democratic Republic of Congo (British Journal of Multidisciplinary and Advanced Studies, 2024)
This article examines the specific challenges encountered by the aeronautical administration of the Airway Authority of the City of Kananga in the Democratic Republic of Congo in the management and consolidation of its aeronautical data, as well as possible solutions to remedy them. We present the different stages of the system deployment process, highlighting the technical, organizational and operational aspects to consider. Finally, the study provides an analysis of the results obtained after the implementation of the data consolidation system, highlighting the benefits and possible remaining challenges.